Exercise effects on bone mineral density in older men: a systematic review with special emphasis on study interventions - Kemmler, Wolfgang; Shojaa, Mahdieh; Kohl, Matthias; von Stengel, Simon (Osteoporosis international, 2018)
This systematic review detected only limited positive effects of exercise on bone mineral density in older men. Further, based on the present literature, we were unable to suggest dedicated exercise prescriptions for this male cohort that might differ from recommendations based on studies with postmenopausal women. The primary aim of this systematic review was to determine the effect of exercise on bone mineral density (BMD) in healthy older men. A systematic review of the literature according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement included only randomized or non-randomized controlled trials of exercise training ≥ 6 months with study groups of ≥ eight healthy men aged 50 years or older, not using bone-relevant pharmacological therapy, that determined BMD by dual-energy X-ray absorptiometry. We searched PubMed, Scopus, Web of Science, Cochrane, Science Direct, and Eric up to November 2016. Risk of bias was assessed using the PEDro scale. We identified eight trials with 789 participants (PEDro-score, mean value 6 of 10) which satisfied our eligibility criteria. Studies vary considerably with respect to type and composition of exercise. Study interventions of six trials were considered to be appropriate for successfully addressing BMD in this cohort. Between-group differences were not or not consistently reported by three studies. Three studies reported significant exercise effects on BMD for proximal femur; one of them determined significant differences between the exercise groups. None of the exercise trials determined significant BMD effects at the lumbar spine. Based on the present studies, there is only limited evidence for a favorable effect of exercise on BMD in men. More well-designed and sophisticated studies on BMD in healthy older men have to address this topic. Further, there is a need to define intervention quality standards and implement a universal scoring system that allows this pivotal determinant to be addressed much more intensively.
EVALuna2:214335